PERBANDINGAN PELAKSANAAN PEMUNGUTAN SUARA ULANG (PSU) DALAM PEMILIHAN KEPALA DAERAH DAN WAKIL KEPALA DAERAH (PILKADA) KABUPATEN PEKALONGAN DAN KEBUMEN TAHUN 2015: STUDI KASUS TPS 1 DAN TPS 2 TIMBANGSARI LEBAKBARANG PEKALONGAN DAN TPS 10 GEMEKSEKTI KEBUMEN - Setya Perdana, Putra Adi; Sardini, Nur Hidayat (Journal of Politic and Government Studies, 2018)
Concurrent elections in Central Java in 2015 are held in as many as 25 (twenty five) Regencies / Municipalities of 35 (thirty five) autonomous regions. In this Regional Election there are a number of problems, one of the interesting issues is the re-election. Regions implementing re-election in the elections of Central Java in 2015 wich is Pekalongan and Kebumen districts, to be exact in voting place 1 and 2 in Timbangsari Village Lebakbarang District Pekalongan Regency and voting place 10 Gemeksekti Village Kebumen. The implementation of the re-election in these two regions has different backgrounds and results so that they have different causal factors. The purpose of this study was to compare the implementation of the re-electon in the two regions to determine the level of voter participation, the shift in the acquisition of voice support before and after the implementation of the re-electionThe method used in this study is qualitative technique with the method of collecting observation data either through interviews or document studies. The selected informants were General Election Commissions of Pekalongan and Kebumen, the district supervisory committee of Pekalongan and Kebumen, executive Committee of Lebarakbarang and Kebumen Subdistricts, Community Leaders of Timbangsari and Gemeksekti Villages.The result of comparison of research shows that there is a shift in the number of votes acquisition and political participation level before and after the implementation of PSU in two different regions. Timbangsari has a high participation rate compared to the implementation of Gemeksekti. The shift of voice occurred only in Timbangsari, with Gemeksekti only a shift in the winner of the ballot recapitulation. Factors causing the implementation of PSU due to violations committed by voters on the basis of ignorance about the form of violations in the election and the negligence of election organizers in performing their duties.Keywords: Regional Election, Re-election, Comparison of Implementation